Dangers in the use of systemic and local drugs expressed in eye disorders - a literature review - Paweł Ziemba; Aleksandra Janocha; Aneta Jerzak; Katarzyna Jakubowska (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose Medications that have been available for many years are commonly used to treat various illnesses. However, nearly all of them can also have toxic effects on other organs, including the eyes, in addition to their therapeutic benefits. In this review, we discuss chosen drug-induced eye disorders, their specific clinical characteristics, and the mechanisms by which certain drugs can damage the ocular system. Isotretinoin and certain chemotherapy drugs are known to contribute to the development of dry eye syndrome. Atimalarial drugs, amiodarone, nonsteroidal anti-inflammatory drugs and chlorpromazine cause the formation of corneal deposits. Prolonged use of glucocorticoids leads to the development of characteristic posterior subcapsular cataracts. The development of cataracts can also be caused by the use of antipsychotic medications. Paradoxically, drugs used topically to treat glaucoma or other eye diseases may trigger an acute attack of angle-closure glaucoma. Materials and methods The methodology for conducting literature search involved utilizing medical subject headings terms to explore PubMed. Search terms included: "drug-induced dry eye disease", "drug-induced cataract", "drug-induced glaucoma", "drug-induced corneal damage". Conclusions Educating patients about the potential ocular side effects of newly introduced treatment is crucial so that they can quickly consult an ophthalmologist if symptoms occur. Adjusting the dosage or discontinuing the drug may alleviate ocular symptoms, but these changes must be considered in light of the overall risk posed by the underlying disease. Every treatment should aim to offer the patient maximum benefits while minimizing any adverse impact on their quality of life.